UPAYA MENINGKATKAN HASIL BELAJAR IPA TERPADU MELALUI PENGGUNAAN MODEL PEMBELAJARAN TIPE THINK PAIR SHARE PADA MATERI PEWARISAN SIFAT TERHADAP SISWA KELAS IX-1 SMP NEGERI 7 MEDAN TAHUN AJARAN 2017/2018 - Nurfuadi Zain (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2020)
The purpose of this study was to determine whether there was an increasein learning outcomes in the biology of hereditary materials through theThink Pair Share (TPS) Cooperative Learning Model. This research is(PTK). In the second cycle, it was found that 94% were declared complete,while 2 students had not yet experienced completeness with an averagescore of 87.33. Thus, in the second cycle the writer concludes that thestudents' scores have reached the KKM score. This research is stopped andthere is no need to continue to the next cycle. Based on the results of thisstudy, it can be concluded that the Think Pair Share (TPS) CooperativeLearning Model has an effect on learning outcomes and there is an increase in the learning outcomes of students in class IX-1 SMP Negeri 7 Medan inthe 2017/2018 academic year.